2014
DOI: 10.20429/ger.2014.110102
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs of Efficacy and Elementary Teachers’ Computational Skills

Abstract: Early mathematics content that is taught in elementary school lays the foundation for students' advanced mathematics performance. Thus, researchers show it is important that pre-service elementary teachers build a strong background in numbers and operations, as well as efficacy beliefs in mathematics instruction. This study expands the literature in the investigation of pre-service teachers' efficacy beliefs and mathematical knowledge by making comparisons of pre-service elementary teachers' views of efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Based on intervew with PSTs shown that they have different experiences on teacher education learning. This is in line with the findings of Hinton et al (2014) that PSTs' number sense skills and computational abilities were not found to be related. Participants can solve mathematical problems using procedures; however they may not know the concepts or the reasons behind the procedures.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Based on intervew with PSTs shown that they have different experiences on teacher education learning. This is in line with the findings of Hinton et al (2014) that PSTs' number sense skills and computational abilities were not found to be related. Participants can solve mathematical problems using procedures; however they may not know the concepts or the reasons behind the procedures.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Wina explains that she takes teacher education program because of not her own desire. Study by Hinton et al (2014) stated that PSTs with lower scores in beliefs also had significantly lower computation scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research conducted in the past on number sense of pre-service teachers has shown that teachers do not possess adequate knowledge in the domain of numbers (Doriney, 2016;Akkaya, 2015;Yaman, 2015;Courtney-Clark and Wessels, 2014;Sengul 2013;Hinton, 2011;Yang et al, 2007). The number sense of pre-service teachers was found to be low and most cases, the pre-service teachers were bound to using rule-based solution strategies.…”
Section: Id Idmentioning
confidence: 99%